2013
DOI: 10.1080/01904167.2013.766804
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Iron and Zinc Quantitative Trait Loci in Soybean for Association to Iron Deficiency Chlorosis Resistance

Abstract: Iron deficiency chlorosis (IDC) in soybean results in yield losses or in extreme cases death. Breeding for resistance has shown limited success with no cultivar having complete resistance. Mineral content of the soybean could be an indicator of the ability of the plant to withstand the effects of IDC. Iron (Fe) and zinc (Zn) concentration was examined in soybean seed and leaves. SSR, RFLP, and BARCSOYSSR markers were used to construct a linkage map used for mapping of Fe and Zn concentrations. The QTL analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 47 publications
(53 reference statements)
1
43
2
Order By: Relevance
“…Using Haldane's mapping function and summing over all linkage groups, there was a total of 2,722.09 cM flanked by linked markers. As reported by (King et al 2012; in press), the average length of the linkage groups was 136.10 cM ranging from 44.71 cM on chromosome 10 to 201.41 cM on chromosome 18. The average length of the marker intervals was 18.15 cM.…”
Section: Construction Of Genetic Linkage Mapsmentioning
confidence: 69%
See 1 more Smart Citation
“…Using Haldane's mapping function and summing over all linkage groups, there was a total of 2,722.09 cM flanked by linked markers. As reported by (King et al 2012; in press), the average length of the linkage groups was 136.10 cM ranging from 44.71 cM on chromosome 10 to 201.41 cM on chromosome 18. The average length of the marker intervals was 18.15 cM.…”
Section: Construction Of Genetic Linkage Mapsmentioning
confidence: 69%
“…The lack of higher marker density on chromosome 10 did not allow the detection of the other phosphate transporter as it was just outside the marker interval. Additionally, it was determined that a ZIP Fe/Zn transporter gene was in a QTL interval, which in previous work (King et al 2012; in press) identified suggestive QTL for both Fe and Zn accumulation and could potentially be a site of metal chelation. There is still work to be done in order to validate these TP QTL regions as well as the genes involved.…”
Section: Discussionmentioning
confidence: 99%
“…The sole but minor effective QTL for Fe concentration on chromosome 3, qFe-3, was approximately co-localized with a QTL that was detected for a Fe efficiency QTL by Lin et al (2000). King et al (2013b) performed QTL analysis for seed P concentration and identified one putative QTL on chromosome 12 and two suggestive QTL on chromosomes 7 and 17. One QTL (qP-17) for seed total P concentration that was identified in our study, with 14.9 % PVE, was at the same chromosomal location as the suggestive QTL on chromosome 17 that was detected by King et al (2013b).…”
Section: Qtl For Mineral Elementsmentioning
confidence: 99%
“…A major QTL accounted for 57.3% of variation for low cadmium (Cd) in soybean (Jegadeesan et al 2010). A major QTL for seed Fe concentration explained 21.5% of the phenotypic variation (King et al 2013). Panthee et al (2006a, b) reported total S-containing amino acids (Cys + Met) with a population average of 1.26/100 g, in addition to detecting three QTLs, one of which explained up to 12.3% of total variation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on understanding genes and processes to improve seed nutritional composition by identifying quantitative trait loci (QTLs) were limited to a few minerals or nutrients in soybean (Jegadeesan et al 2010;King et al 2013;Panthee et al 2006a;Zhang et al 2009). Four QTLs for seed Ca concentration were detected, one of which accounted for up to 16.3% of variation (Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%